GRP-070 Evaluation of the Effect on Patient Safety of a New Label Design For Medicinal Products. (12th March 2013) - Fischer, H; Clemmensen, MH; Kart, T; Dieckmann, P; Kunstek, P; Schytte-Hansen, S; Hellebek, A
Abstract : Background: In Denmark some of the medicinal products for hospitals are produced by the hospital pharmacies and registered by Amgros (SAD products). In 2007 the Danish Society for Patient Safety, Amgros, and the private foundation TrygFonden organised a design competition with the purpose of improving patient safety in label design. The winner "Medilabel Safety System" was designed by e-Types and incorporated 9 design features. The new labels were implemented in 2008. Purpose: To evaluate the effects of the new label design on patient safety. Materials and Methods: Reports of medication errors related to SAD products before and after the introduction of the new design (2007 and 2010) were compared. Medication errors were obtained from the Danish Patient Safety Database (DPSD). In another study patient simulation and a sorting exercise were used to evaluate the effects of the new design. 11 physicians and 9 nurses participated. Results: In 2007 and 2010 a total of 6781 and 10188 medication errors were reported to DPSD. Of these, 85 (2007) and 80 (2010) dispensing errors could be related to misinterpretation of the SAD label. Thus, while no overall effect on the number of errors related to SAD products could be observed, the relative decrease could indicate a positive effect. The simulation study indicated that specific design features such as yellow background colour, Tall Man lettering and consistent design improved safety in the medication process. However, the new label design is complex implying a potential for misinterpretation of the features if the users are not familiar with the design. Conclusions: The effect of the new design depends on several factors such as the user's knowledge of the design, the complexity of the design and the context of use. Errors related to misinterpretation of labels remains a problem and research into good label design remains a relevant topic. No conflict of interest.